O JORNALISMO DA FONTE COMO PARTE NECESSÁRIA DE UM JORNALISMO PLURAL DEMOCRÁTICO – AS ROTINAS DA DIVULGAÇÃO DA ASSEMBLEIA LEGISLATIVA DO PARANÁ - Santos Júnior, Edson Gil (2015)
This study uses the labor practices of the diffusion sector of Assembleia Legislativa do Paraná (Alep) and consequently the TV Sinal that produces the journalistic content of the said institution site, to give an overview of the work done for the people and identify if the work is of journalism, media relations or journalism source. Taking into account the current Brazilian legislation, the use of digital technologies such as the change of the behavior of professionals. For this, the research uses a methodology with various techniques, for example, content analysis, participant observation and in-depth interviews to discern in what moments the work of these journalists can be considered a corporate communication or public communication since the cost of this structure comes from the taxpayer and from not the head of the legislature. The result points to a journalism source and media changing in Alep, due to increased transparency of public data, as well as using objectivity as a tool to achieve credibility and so, in a pluralized journalism context, the great demand information available to consolidate as a reliable expert reference, compared to other means to address the legislative public issue.